Field response and quality evaluation of alfalfa varieties for dehydrated forage production - Corsi G.; Dal Re L.; Laffi G.; Ligabue M. (Quality in lucerne and medics for animal production, 2001)
A field trial has been carried out during the three year period 1998-2000 around Ravenna (Adriatic coast), to examine: (i) alfalfa cultivar response to climatic and soil characteristics, with a cutting schedule based on a fixed number of days (28); and (ii) forage quality changes caused by high temperature drying. Seven cultivars were included in the experiment: Selene, Superba, Triade, Zenith, Classe, Zenith and Prosementi (test), arranged in a randomized block design in small plots. Dry matter yield was determined. The same cultivars were sown also in large plots, to produce for each variety such quantities of forage sufficient for the dehydrator. Crude protein and fiber, total ash, NDF, ADF, ADL were determined before and after conservation. In this paper yield data and quality evaluation of the three year period are presented.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)